2011
DOI: 10.1128/mcb.01189-10
|View full text |Cite
|
Sign up to set email alerts
|

A KLF4–miRNA-206 Autoregulatory Feedback Loop Can Promote or Inhibit Protein Translation Depending upon Cell Context

Abstract: Krüppel-like factor 4 (KLF4), a transcription factor that regulates cell fate in a context-dependent fashion, is normally induced upon growth arrest or differentiation. In many cancer cells there is dysregulation, with increased expression in proliferating cells. To identify sequence elements that mediate KLF4 suppression in normal epithelial cells, we utilized a luciferase reporter and RK3E cells, which undergo a proliferationdifferentiation switch to form an epithelial sheet. A translational control element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 66 publications
5
120
0
2
Order By: Relevance
“…It was also found that miR-145 mediates myocardin gene upregulation during muscle differentiation (41). Cell type and growth conditions may dictate gene expression upregulation or downregulation (42). Upregulation of mRNA transcription or translation may involve miRNA binding to 59UTR of the mRNA (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that miR-145 mediates myocardin gene upregulation during muscle differentiation (41). Cell type and growth conditions may dictate gene expression upregulation or downregulation (42). Upregulation of mRNA transcription or translation may involve miRNA binding to 59UTR of the mRNA (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle microRNAs in development and disease [102,106] , metastatic lung tumors [107] , proliferating breast cancer [108] , ERαpositive breast cancer [109] , EEC [110] , NSCLC [85] , TSCC [111,112] , laryngeal SCC [113] , and HNSCC [114] (Table 3). Many of the reports identify reduction in a single myomiR, but in case studies of particular cancers often the different myomiRs have been identified as downregulated, for example in NSCLC tumor samples, miR1 [100] , 133a [85,115] , 133b [85,115] , 206 [107] or miR1/206 [99] have been reported, by implication dysregulation of all of the myomiRs.…”
Section: Cancer and Downregulated Myomirsmentioning
confidence: 99%
“…Importantly, key targets of miR12 and 206 include enzymes of the pentose phosphate pathway (including G6PD, PGD and TKT) and the tricarboxylic acid cycle enzyme GPD2, which increase their activities and potentiate cancer cell proliferation and compromise patient survival. Pleiotropic factors, such as KLF4, HDAC4 and IGFR1 are also elevated in gastric carcinoma and in breast cancer cells in part due to the loss of miR206 [108] , yet in contrast KLF4 is reduced in colon cancer tissue due to strong upregulation of 206 [116] . KLF4 is a zinc-finger transcription factor that binds to the TGFβ1 promoter and is important during normal cellular differentiation and proliferation.…”
Section: Other Pleiotropic Pathwaysmentioning
confidence: 99%
“…Related miRNAs such as miR-10a and miR10b have hundreds of common targets (Martin et al 2014). miR-206 competes with miR-344 for the MRE which is the translational control element inside the 3 ′ UTR thereby promoting or repressing KLF4 expression (Lin et al 2011). miR101a and miR-199a * bind to 3 ′ UTR of Cox-2 mRNA thereby controlling its expression (Chakrabarty et al 2007).…”
Section: Introductionmentioning
confidence: 99%